Weak effects of common genetic variation in oxytocin and vasopressin receptor genes on rhesus macaque social behavior - Madlon-Kay, Seth (Am J Primatol, 2018)
The neuropeptides oxytocin (OT) and arginine vasopressin (AVP) influence pair bonding, attachment, and sociality, as well as anxiety and stress responses in humans and other mammals. The effects of these peptides are mediated by genetic variability in their associated receptors, OXTR and the AVPR gene family. However, the role of these genes in regulating social behaviors in non-human primates is not well understood. To address this question, we examined whether genetic variation in the OT receptor gene OXTR and the AVP receptor genes AVPR1A and AVPR1B influence naturally-occurring social behavior in free-ranging rhesus macaques—gregarious primates that share many features of their biology and social behavior with humans. We assessed rates of social behavior across 3,250 hr of observational behavioral data from 201 free-ranging rhesus macaques on Cayo Santiago island in Puerto Rico, and used genetic sequence data to identify 25 OXTR, AVPR1A, and AVPR1B single-nucleotide variants (SNVs) in the population. We used an animal model to estimate the effects of 12 SNVs (n = 3 OXTR; n = 5 AVPR1A; n = 4 AVPR1B) on rates of grooming, approaches, passive contact, contact aggression, and non-contact aggression, given and received. Though we found evidence for modest heritability of these behaviors, estimates of effect sizes of the selected SNVs were close to zero, indicating that common OXTR and AVPR variation contributed little to social behavior in these animals. Our results are consistent with recent findings in human genetics that the effects of individual common genetic variants on complex phenotypes are generally small.